2022
DOI: 10.1016/j.drugpo.2021.103573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating how has care been affected by the Ontario COVID-19 Opioid Agonist Treatment Guidance: Patients’ and prescribers’ experiences with changes in unsupervised dosing

Abstract: Background The COVID-19 pandemic has exacerbated the opioid crisis. Opioid-related deaths have increased and access to treatment services, including opioid agonist treatment (OAT), has been disrupted. The Ontario COVID-19 OAT Treatment Guidance document was developed to facilitate access to OAT and continuity of care during the pandemic, while supporting physical distancing measures. In particular, the Guidance expanded access to unsupervised OAT dosing. It is important to evaluate the changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
1
25
0
3
Order By: Relevance
“…The relatively static level of OAT enrollment post-implementation is likely owed to the immediate and sustained increase in the proportion of OAT-enrolled participants receiving take-home doses and the immediate, albeit temporary, decrease in the proportion undergoing weekly urine drug screening. Specifically, the increased likelihood of receiving take-home doses following the OAT modifications and corresponding decreased likelihood of routine urine drug screening (at least initially) may have facilitated treatment retention despite pandemic restrictions by reducing OAT patients’ in-person clinical encounters and affording greater flexibility in their dosing schedules ( Corace et al, 2022 ; Haasen & Brink, 2006 ; Sarasvita et al, 2012 ; Schaub et al, 2010 ). These post-implementation changes are likely attributable to the provincial interim treatment guidance, which explicitly recommended that prescribers and pharmacists reduce the frequency of urine drug screening and observed doses for OAT patients during the COVID-19 pandemic ( Centre for Addiction and Mental Health et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively static level of OAT enrollment post-implementation is likely owed to the immediate and sustained increase in the proportion of OAT-enrolled participants receiving take-home doses and the immediate, albeit temporary, decrease in the proportion undergoing weekly urine drug screening. Specifically, the increased likelihood of receiving take-home doses following the OAT modifications and corresponding decreased likelihood of routine urine drug screening (at least initially) may have facilitated treatment retention despite pandemic restrictions by reducing OAT patients’ in-person clinical encounters and affording greater flexibility in their dosing schedules ( Corace et al, 2022 ; Haasen & Brink, 2006 ; Sarasvita et al, 2012 ; Schaub et al, 2010 ). These post-implementation changes are likely attributable to the provincial interim treatment guidance, which explicitly recommended that prescribers and pharmacists reduce the frequency of urine drug screening and observed doses for OAT patients during the COVID-19 pandemic ( Centre for Addiction and Mental Health et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early Canadian data further indicate that most people who received additional carries were no more likely to experience adverse outcomes (e.g., self-reported opioid overdoses, emergency department visits, etc.) than those who did not receive carries [ 74 , 75 ]. However, most clinicians reported that they prescribed carries to patients only when they felt sure of the patient’s social and housing stability, which means that the perpetuation of inequitable access to OAT carries still exists for some high-risk populations, even during a period of loosened OAT carry prescription policies.…”
Section: Importance Of Access To Oat Carries For Individuals With Oud...mentioning
confidence: 99%
“…In response to these challenges, Ireland, like many other countries, developed a rapid and coordinated response to accelerate new ways of meeting the treatment needs of people with opioid dependency, documented in a suite of national contingency guidelines by the Health Service Executive (HSE) ( Hennigan, Corrigan, Killeen, Scully, & Keenan, 2021 ; Krawczyk, Fawole, et al, 2021 ; Mongan, Galvin, Farragher, Dunne, & Nelson, 2020 ). The priority was to facilitate rapid access or low threshold pathways to OAT for those not already in treatment, while ensuring that existing patients’ care was uninterrupted ( Corace et al, 2022 ; Hennigan et al, 2021 ; Khatri & Perrone, 2020 ; Krawczyk, Fawole, et al, 2021 ; O'Carroll, Duffin, & Collins, 2021 ). The contingency guidelines supported accelerated access to OAT, particularly for the homeless, and included increased access to buprenorphine.…”
Section: Introductionmentioning
confidence: 99%